[updated from 2017] Aflasafe MWMZ01 product for Malawi and Mozambique - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Aflasafe MWMZ01, a biocontrol product developed for use in maize and groundnut in Malawi and Mozambique, has reached the final stage of piloting. Registration dossiers have been submitted to the regulatory authorities in both countries.